(untitled) (Geologica Macedonica, 2019)
The results of a study on the presence and enrichment of potentially toxic elements in surface soil in the Mitrovica region, Kosovo, are reported. The investigated region (301.5 km2) was covered by a sampling grid of 1.4×1.4 km and a total of 156 soil samples were collected. Inductively coupled plasma - mass spectrometry (ICP-MS) was applied for the determination of anthropogenic association of 12 elements: Ag, As, Au, Bi, Cd, Cu, Hg, Pb, Mo, Sb, Tl and Zn. For data evaluation, parametric and non-parametric statistics methods were used. Soil contamination is assessed on the basis of enrichment factor (EF). The average content of Pb was 19.6-fold; Cd 11-fold; Hg 5-fold; Zn 4.5-fold; As 4.3-fold; Sb 3.8-fold; Cu 3.2-fold and Ag 1.6-fold higher that European average values. Increased levels of the content of these metals showed that mining and smelter processing activities strongly affected in soils of the towns of Zveçan and Mitrovica and their environs. In the close vicinity of the cities of Zveçan and Mitrovica, the contents of the As, Cd, Cu, Pb and Zn were even higher than the corresponding intervention values according to the New Dutch list and were exceed in 122 km2 of the investigated area. Key words: soil pollution; potentially toxic elements; Mitrovica; Republic of Kosovo